Comparisons of Antecedents of Trailblazing/Adoption and Quantitative/Qualitative Studies of Public Policy Innovation Identified in a Systematic Literature Review – IV - Glor, Eleanor D (Innovation Journal, 2021)
Are the antecedents identified in trailblazing/adoption and quantitative/qualitative public policy innovation studies similar or different? This quantitative study answers this question by identifying, categorizing and analyzing their antecedents, identified in a systematic literature review (SLR). Trailblazing is the first three adoptions of an innovation in its population/ community, adoption is all adoptions, in any organization. If their antecedents were different, this would lend credibility to the idea that they are different phenomena. The criteria for inclusion in the SLR were met by 87 publications; 594 antecedents were identified. Analysis identified 508 unique antecedents, 28 grouped antecedents, 5 factors and 3 clusters.